Oculokinetic perimetry: a simple visual field test for use in the community. Issue 12 (December 1985) - Damato, B E
Abstract : A method of visual field examination is described which enables an unsupervised person to carry out self-assessment using only a paper test chart, a record sheet, and a pencil. It is entitled 'oculokinetic perimetry' because it is the subject's eye that moves and not the test target. By providing non-ophthalmic health care workers with a simple means of performing perimetry in the community, and by allowing susceptible people to carry out self-assessment of the visual fields at home, this test should facilitate the detection and management of glaucoma, especially in underdeveloped countries.